REPERE EMBLEMATICE ALE TURISMULUI BLĂJAN (PANGEEA, 2025)
ABSTRACT: Tourism Landmarks of Blaj City. Blaj City, located at the confluence of the rivers Târnave, is an ancient cultural center of Transylvania and Romania. Here they founded the first Romanian schools, the centerpiece of the Greek-Catholic Church and different historical events occurred related to the revolution of 1848. All these events are highlighted by several major tourist attractions, which are presented in the paper: Cultural Palace, “Holy Trinity” Cathedral, Liberty Plain linden tree of Eminescu, The Cross of Iancu, Oak of Iancu, The History Museum and The Metropolitan Castle.
Keywords: tourism potential; cultural; historical; natural monuments